APLIKASI KAMUS BAHASA INGGRIS DILENGKAPI DENGAN FASILITAS TEKNOLOGI TEXT TO SPEECH BERBASIS ANDROID - Ika Sari (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2018)
The ability of the android opening system on the mobile device is getting the day has provided a range of benefits to the application developer. Text to speech is one of android technologi whose benefits are widely used to help a job. In principle, the system TTS (Text To Speech) is a system that can do the conversion from text to speech. In this study, the author intends to design and produce a media application as a tool for learning English, especially in SDN 107400 by utilizing technology to speech as its text. Applications will be aimed at students using smartphone media, especially smartphone with android operating system. The application of text to speech will be used as tools in understanding of various materials as well as the conversations that have been provided applications. With this feature expected in learning English, especially in everyday conversation can be easily done and understood why text to speech will provide an understanding of its users directly via voice.